International Standards In Green Bond Regulation: A Comparative Study of Indonesia and The Philippines - Pranata, Dendy Erdi; Endarto, Budi (Journal of Law, Politic and Humanities, 2025)
The integration of international legal principles and standards into Indonesian regulations has expanded significantly, particularly within the field of contemporary law. A notable area of development is the regulation of green bonds as a sustainable financing instrument in Indonesia, which is guided by principles formulated by the International Capital Market Association (ICMA) and standards established by the ASEAN Capital Market Forum (ACMF). This study examines how legal frameworks and the legal justification for adopting international standards are applied to green bond regulation in Indonesia and the Philippines. The research adopts a normative legal approach, employing statutory, conceptual, and comparative methods. Its objective is to identify the applicable regulations and to analyze the rationale underlying the incorporation of international principles and standards in green bond governance in both countries. The findings reveal that green bond regulation in Indonesia under POJK 18/2023 and in the Philippines under SEC Memorandum Circular No. 12, Series of 2018, represents a harmonization of ICMA’s Social Bond Principles with the ASEAN Social Bonds Standards. From an international law perspective, the use of ACMF standards is grounded in the Vienna Convention on the Law of Treaties 1986, reflecting a theoretical inclination toward universalist protectionism.